Značilnosti funkcioniranja odvisnih družin in čustvena kompetentnost oseb, odvisnih od psihoaktivnih snovi - Dular, Katja (Rehabilitacija (Ljubljana), 2013)
Introduction: Many changes that drug addiction brings to persons cognitive, emotional and behavioural level multiply and complicate inside of the family system. Researchers have found out that functional family dynamics and person's ability to regulate their own emotions predicts better outcome in substance abuse treatments. We predict that families with drug abusing person function less healthily; that drug abusing person has less competence to regulate their emotions; and that they experience more traumatic events than people without addiction. Methods: The study included drug abuse clients (clinical group) who were included in the treatment at the Psychiatric Clinic Ljubljana Centre for Treatment of Drug Addiction (N = 101) and those without addiction or any other psychiatric illness (control group) (N = 96). We applied two questionnaires - the Family Environment Scale (FES) and the Emotional Intelligence, Skills and Competences Questionnaire (ESCQ), as well as sociodemografic questions. Groups were statistically compared using paired t-test and Mann-Whitney test. Results: Statistically significantly lower values were observed in families of drug abusing persons on the majority of the measured dimensions of family functioning (cohesion, expressiveness, independence, intellectual and cultural activities, active and recreational orientation, organization), and a higher degree of conflicts than the in families without drug abuse. Drug abusing persons showed more difficulties in the field of expressing and regulating emotions and had overall lower emotional competences. Substance abusing persons had more often been abused or had experienced trauma in past. Conclusion: The results point to the risk factors for development of substance use disorder, and we may assume the importance of engaging in family therapy for substance abuse treatments.The study highlights the need to address the risk factors at each level of working with drug abusing persons.
Keywords: čustvena kompetentnost; dejavniki tveganja; družina; emotional competence; family; family functioning; funkcioniranje družine; odvisnost; psychological trauma; Risk Factors; Substance-Related Disorders; travmatiziranost; zloraba drog